2022
DOI: 10.1088/1741-4326/ac74d1
|View full text |Cite
|
Sign up to set email alerts
|

Edge biasing and its impact on the edge and SOL turbulence

Abstract: A theoretical study is made of the effect of edge biasing on the dynamics of the interchange turbulence in the edge and scrape-off layer (SOL) regions. A linear analysis of a set of model fluid equations shows that biasing stabilizes the small ky modes. The model equations are next solved numerically, using the BOUT++ framework, to explore the nonlinear dynamics in the presence of positive or negative bias and compared to results in the absence of bias. Positive biasing is found to lead to a larger increment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The radial profiles of the particle flux (Γ) for w/ and w/o mobility have been shown in figure 6 using Λ b = +64 volt which is indicated by the blue-colored solid and black-colored dashed lines. It has been observed from figure 6 that the effect of mobility increases Γ in the edge region and decreases in the SOL region [30]. This is also a reason behind the reduction in the plasma density and electron temperature for the positive edge biasing (figures 2(a) and (c)).…”
Section: Simulation Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…The radial profiles of the particle flux (Γ) for w/ and w/o mobility have been shown in figure 6 using Λ b = +64 volt which is indicated by the blue-colored solid and black-colored dashed lines. It has been observed from figure 6 that the effect of mobility increases Γ in the edge region and decreases in the SOL region [30]. This is also a reason behind the reduction in the plasma density and electron temperature for the positive edge biasing (figures 2(a) and (c)).…”
Section: Simulation Resultsmentioning
confidence: 72%
“…The model equations related to edge biasing had been discussed in [30,31], where it was found that the high positive biasing voltages led to a high radial electric field and its shear that greatly reduced the turbulence in the edge and SOL regions. It was found that these simulations did not allow the application of very high biasing voltages at the electrode [30,31] as at higher voltages the plasma turbulence was seen to almost disappear. In reality, the experimental edge biasing has been performed for significantly higher biasing voltages where the plasma turbulence is still present.…”
Section: Model Equationsmentioning
confidence: 99%
See 3 more Smart Citations